Integration of OHSMS and Marketing Strategies in Shipbuilding: Literature Review and Its Implications on Productivity - Melani Quintania; Mohammad Danil Arifin (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The shipbuilding industry is characterized by high-risk working environments, making the implementation of Occupational Health and Safety Management Systems (OHSMS) critically important. While OHSMS has traditionally been regarded as a tool for regulatory compliance, recent studies suggest can also function as a strategic asset that enhances a company's market positioning. This paper aims to investigate the integration of OHSMS with marketing strategies in the shipbuilding industry and evaluate their combined impact on productivity. A systematic literature review was conducted, analyzing 40 selected sources including peer-reviewed journal articles, industry reports, and regulatory frameworks. The review reveals that companies that strategically align their safety management systems with marketing communications tend to achieve multiple benefits, such as improved safety performance, stronger client trust, enhanced brand reputation, and increased productivity. These findings support the growing perspective that occupational health and safety can serve not only as an internal operational necessity but also as a competitive differentiator. The study contributes to the literature by highlighting the untapped potential of safety performance as a component of industrial marketing and suggests that cross-functional collaboration between health and safety and marketing teams can deliver both operational and reputational advantages.